2005
DOI: 10.1007/s10595-005-0117-1
|View full text |Cite
|
Sign up to set email alerts
|

Studies on ZnS Nanoparticles Prepared in Aqueous Sodium Dodecylsulphate (SDS) Micellar Medium

Abstract: ZnS, a large band gap material, is useful in electro-luminescence and optoelectronic devices. We herein report a method for preparation of nanosized ZnS particles in micellar medium of anionic surfactant sodium dodecylsulphate. The optical properties of the prepared ZnS nanoparticles have been studied by absorption and fluorescence methods. Electron microscopic characterization has evidenced triangular particles, an uncommon observation in the synthesis of nanomaterials. PVC membrane containing nano ZnS disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…Both ZnS and MnS crystals efficiently scavenge UV up to approximately 320 nm (81,87). The molar absorption coefficient of ZnS particles is approximately 2 mM cm −1 at 260 nm, at which nucleotides absorb (88). It is easy to estimate that a thin, 5-μm layer of ZnS would attenuate the UV light by a factor of 10 10 .…”
Section: Vapor-dominated Zones Of Terrestrial Geothermal Systems Asmentioning
confidence: 99%
“…Both ZnS and MnS crystals efficiently scavenge UV up to approximately 320 nm (81,87). The molar absorption coefficient of ZnS particles is approximately 2 mM cm −1 at 260 nm, at which nucleotides absorb (88). It is easy to estimate that a thin, 5-μm layer of ZnS would attenuate the UV light by a factor of 10 10 .…”
Section: Vapor-dominated Zones Of Terrestrial Geothermal Systems Asmentioning
confidence: 99%
“…The finite-depth model proposed by Nakaoka and Nosaka is reported in Fig. 1 (full line curve), together with the literature data collected in their work and in other studies [31,34,38]. The same set of literature data was employed by Calandra et al to propose an empirical correlation following the power law [36]: …”
Section: Resultsmentioning
confidence: 98%
“…Many stabilizing agents have been reported in the literature for the synthesis of QD, including various surfactants, organic or inorganic polymers, thiols, amines and polyphosphates [21][22][23][24][25][26][27]. The use of ''water in oil'' (w/o) microemulsions has proved to be a promising approach to synthesize and stabilize size-controlled nanoparticles in reverse micelles confined spaces [28][29][30][31][32][33][34]. Water in oil microemulsions are composed of heterogeneous systems of reverse micelles with water in their hydrophilic core, dispersed in nonpolar environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on synthesis and physical properties of PVC based nanocomposite have been reported by many researchers such as PVC/montmorillonite (MMT) [13], PVC/ZnO [14], PVC/ CNT [15,16], PVC/CaCO 3 [17], PVC/ZnS [18], PVC/Cd (ZnO) [19], PVC/CdS [20], PVC/organo-clay [21] etc. It has been observed that the incorporation of nanomaterials into PVC improves the thermal stability, glass transition temperature, specific heat and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%